Penafsiran Amilenialisme & Teologi Kovenan Dalam Memahami Alkitab - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
There are various choices in understanding the Bible to become dogma in a church. Whether it was built based on a guide from the Bible and the traditions of the apostles or church fathers, to those who only focus on the Bible. Those based only on the Bible also have their own uniqueness. Amillennialism believes that the church is in the entire Old Testament. Paul, for example, uses the church that leads to Israel (Gal. 6:16). In addition, the remnants of the Israelites in the OT were said to be the church (Acts 7:38). The church is already in the OT with the election of the nation of Israel to be God's people. Even further, followers of amillennialism believe that the church existed in the garden of Eden. Covenant theology bases its theological understanding and the study of the Bible is based on three covenants namely the work agreement, redemption and grace. Covenant theology can be said to be a new theology, not even in the days of the church fathers. Even so, Augustine did mention the relationship of Adam, who at first, stood before God as a covenant. The exposition of the book of Revelation, according to the Covenant Theologian, is based on the method of progressive parallelism which is divided into seven parts. The seven parts are parallel with each other. Each section also reveals a certain progression in the process of eschatology. Although the book of Revelation is divided into seven parts, it should not only pay attention or focus on one part, but should appreciate all parts of the book of Revelation as a whole. Abstrak Indonesia Ada aneka pilihan di dalam memahami Alkitab untuk bisa menjadi dogma dalam sebuah gereja. Entah yang dibangun berdasar perpanduan dari Alkitab dan tradisi para rasul atau bapa gereja, hingga yang hanya fokus kepada Alkitab semata. Yang mendasarkan pada Alkitab saja, juga memiliki keunikannya masing-masing. Kaum amilenialisme meyakini bahwa gereja sudah ada di dalam seluruh Perjanjian Lama. Paulus, contohnya, memakai gereja yang mengarah kepada Israel (Gal. 6:16). Di samping itu, sisa-sisa orang Israel di dalam PL dikatakan sebagai gereja (Kis. 7:38). Gereja sudah ada di dalam PL dengan pemilihan bangsa Israel menjadi umat Allah. Bahkan lebih jauh lagi, penganut amilenialisme percaya bahwa gereja sudah ada ketika di taman Eden. Teologi kovenan mendasarkan pemahaman teologis maupun penelahaan Alkitabnya berdasarkan dari tiga perjanjian yaitu perjanjian kerja, penebusan dan anugerah. Teologi perjanjian dapat dikatakan suatu teologi yang baru, bahkan belum ada pada masa bapa-bapa gereja. Meskipun demikian, Agustinus memang pernah menyinggung hubungan Adam, yang pada mulanya, berdiri di hadapan Allah sebagai perjanjian. Eksposisi kitab Wahyu, menurut Teolog Kovenan, didasarkan pada metode paralelisme progresif yang terbagi menjadi tujuh bagian. Ketujuh bagian tersebut bersifat paralel satu dengan lainnya. Masing-masing bagian juga menyingkapkan akan progresivitas tertentu dalam proses eskatologi. Meskipun kitab Wahyu terbagi atas tujuh bagian, namun tidak boleh hanya memperhatikan atau terfokus pada satu bagian saja, tetapi hendaknya menghargai semua bagian dalam kitab Wahyu sebagai keseluruhan.